INFLUENCE OF MORAL VALUES ON THE SUCCESS OF ECONOMIC ACTIVITY (ON THE EXAMPLE OF DOMESTIC ENTREPRENEURS OF THE XIX-XX CENTURIES) - E. V. Gladysheva (Российский технологический журнал, 2017)
The article deals with the problem of combining economic activity and moral principles. Today students often believe that the market economy is incompatible with the morality, the topicality of this topic is grounded in the pedagogical and educational activity of teachers. The steps in this direction are indicated by Moscow Technological University, G.V. Plekhanov Russian Economic University. An article by O.A. Volnyakova on this topic is analyzed. The author of the article analyzes the moral qualities of the native entrepreneurs of the 19th-20th centuries, which contributed to their successful economic activity. It is concluded that the economic success of native entrepreneurs was largely related to such qualities as honesty, diligence, patience, thrift, striving for learning, innovation, philanthropy and charity. The article points out that Russian merchants aspired not only to economic gain, but also to spiritual values. The author of the article shows the modern development of this topic in social entrepreneurship, which only starts developing in our country. The author of the article tells how the theme of the moral dimension of the economy is used by the staff of the Department of Philosophy, Sociology and Political Science of MTU in their pedagogical and educational work with students. This topic can be used by other employees of the Moscow Technological University.